Cooperation Mechanism of Wide-area Protection System Based on Multi-Agents - Mingzhu Zhang; Zhenxing Li (Institute of Advanced Engineering and Science, 2013)
With the rapid growth of power system, it is becoming increasingly difficult to realize reach and time coordination for conventional backup protection. To cope with those problems, wide-area protection is widely researched. In this paper, a novel dynamic cooperation mechanism of wide-area protection is proposed, which can operate better than distributed and centralized systems with respect to reliability, section selectivity, and so on. The multi-agents technology is used to enhance adaptability and decrease communication traffic of wide-area protection system. The improvement of backup protection performance to overcome some specific conditions, such as communication bit error, protection failure, and breaker failure, is also illustrated by utilizing communication networks and distributed protection agents which enables an easy and flexible construction and operation of the proposed wide-area protection system. The example analysis on IEEE 5 nodes system shows the concrete cooperation processing among agents in the cases of typical faults. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1888